Fine Motor Development for Children Aged 4-6 Years by Using Woven Products in Kampung Purun - Rusmaniah Rusmaniah; Celia Cinantya; Muhammad Ridha Ilhami (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2022)
One of the aspects of child development is fine motor skills. Children's fine motor skills are essential to be stimulated from an early age. Fine motor skills can be trained by using learning media so that learning becomes more fun. This research aims to describe the children's fine motor development aged 4-6 years using woven media in Kampung Purun. This research uses a qualitative approach. Data collecting by interviews, observation, and documentation. Data analysis through the reduction stage, presentation, and conclusion and it’s verified. The research results explain that purun woven product media coloring activities can improve children's fine motor skills aged 4-6 years.  . Implications for children's fine motor development are : 1) train in writing preparation, 2) stimulate the development of social, emotional, and artistic aspects, 3) train children's creativity so that children become creative and dare to try. 4) train children to think logically in relation to the ability to count. This research makes it easier for PAUD teachers to use woven products as learning media for early childhood in helping develop their fine motor skills.